A BIBLIOMETRIC REVIEW AND ANALYSIS ON IMPULSIVE SUICIDAL BEHAVIOUR - Nurasikin Mohamad Shariff; Sharifah Munirah Syed Elias; Norlinda Abd. Rashid; Nur Ain Mahat; Wan Hasliza Wan Mamat (Journal of Islamic, Social, Economics and Development, 2024)
This bibliometric analysis delves into the extensive research on impulsive suicidal behavior, specifically emphasizing its multifaceted nature and its implications for preventing suicide. In the introduction, we provide context for the growing recognition of impulsivity as a critical factor in understanding suicidal behaviors. We then proceed to describe our methodology, which involves content analysis to synthesize and appraise the diverse literature on impulsive suicidal behavior. Our aim with this analysis is to pinpoint significant themes, trends, and areas for further investigation within the literature, offering insight into where more research is needed. Our findings underscore the importance of interdisciplinary collaboration and evidence-based approaches in addressing impulsive suicidal behavior and advancing suicide prevention efforts. Overall, this study contributes to the ongoing discourse on mental health and suicide prevention by providing insights into the complex interplay between impulsivity and suicidal behaviors. The implication for mental health services is to deepen our understanding of impulsive suicide to lessen its profound impact on individuals, families, and communities. This, in turn, can promote evidence-based practices and foster interdisciplinary collaboration. By integrating insights from this bibliometric analysis, mental health services can align with WHO recommendations to prioritize interventions that target impulsivity, thereby reducing the incidence of impulsive suicidal acts and ultimately saving lives.